1999
DOI: 10.1073/pnas.96.21.11854
|View full text |Cite
|
Sign up to set email alerts
|

β2-Chimaerin is a novel target for diacylglycerol: Binding properties and changes in subcellular localization mediated by ligand binding to its C1 domain

Abstract: The members of the chimaerin family of Rac-GTPase-activating proteins possess a single C1 domain with high homology to those present in protein kinase C (PKC) isozymes. This domain in PKCs is involved in phorbol ester and diacylglycerol (DAG) binding. We previously have demonstrated that one of the chimaerin isoforms, ␤2-chimaerin, binds phorbol esters with high affinity. In this study we analyzed the properties of ␤2-chimaerin as a DAG receptor by using a series of conformationally constrained cyclic DAG anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
104
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 39 publications
8
104
0
2
Order By: Relevance
“…To this end we generated three mutant proteins: one containing a point mutation in the C1 domain that disrupts phorbol-ester binding (C114A) (23); one containing a point mutation in the GAP domain (R179G) that abolishes Rac-GAP activity (21,24); and a deletion mutant in which the entire GAP domain was deleted (⌬GAP). To confirm Rac-GAP activity of the two point mutants we performed GTPase pull-down assays with the Rac effector (CRIB) domain of the serine͞threonine kinase PAK1, which selectively affinity purifies the GTP-bound form of Rac (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end we generated three mutant proteins: one containing a point mutation in the C1 domain that disrupts phorbol-ester binding (C114A) (23); one containing a point mutation in the GAP domain (R179G) that abolishes Rac-GAP activity (21,24); and a deletion mutant in which the entire GAP domain was deleted (⌬GAP). To confirm Rac-GAP activity of the two point mutants we performed GTPase pull-down assays with the Rac effector (CRIB) domain of the serine͞threonine kinase PAK1, which selectively affinity purifies the GTP-bound form of Rac (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identities of the Ser316 kinase and Ser325 phosphatase acting downstream of PKC have yet to be identified but these studies have ruled out PKA and mitogen-activated protein kinases in this process. In addition to the phorbol ester-binding PKC isoenzymes, PMA has been reported to bind other receptors such as the chimaerins (Caloca et al, 1999), Ras guanyl-releasing protein (ElShemerly et al, 1997;Ebinu et al, 1998) and protein kinase Ds (Van Lint et al, 2002). Importantly, this study and previous studies (Legg et al, 2002) have demonstrated that the effects of PMA treatment on CD44 Ser316 phosphorylation and Ser325 dephosphorylation are mediated via activation of PKC as the PKC inhibitors Ro-31 and Bis-I are effective in blocking these phosphorylation/dephosphorylation events.…”
Section: Discussionmentioning
confidence: 99%
“…DAG can act as a membrane recruitment signal and activator for a series of signaling proteins, e.g. it has been shown that plasma membrane DAG is vital for the activation of some PKC isoforms (38), UNC-13 (39), RasGRP (40), and chimeras (41). The DAG-mediated control of these signaling proteins underlies its role in affecting cell proliferation, differentiation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%